Use of National Early Warning Score for observation for increased risk for clinical deterioration during post-ICU care at a surgical ward - Klepstad PK; Nordseth T; Sikora N; Klepstad P (Dove Medical Press, 2019)
Pia Katrin Klepstad,1 Trond Nordseth,2,3 Normunds Sikora,4 Pål Klepstad2,5 1Faculty of Medicine, Riga Stradins University, Riga, Latvia; 2Department of Circulation and Medical Imaging, Faculty of Medicine and Health Sciences, Norwegian University of Science and Technology, Trondheim, Norway; 3Department of Emergency Medicine and Pre-hospital Services, St Olav University Hospital, Trondheim, Norway; 4Department of Surgery, Riga Stradins University, Riga, Latvia; 5Department of Anesthesiology and Intensive Care Medicine, St Olav University Hospital, Trondheim University Hospital, Trondheim, Norway Purpose: Patients transferred from an intensive care unit (ICU) to a general ward are at risk for clinical deterioration. The aim of the study was to determine if an increase in National Early Warning Score (NEWS) value predicted worse outcomes in surgical ward patients previously treated in the ICU. Patients and methods: A retrospective observational study was conducted in a cohort of gastrointestinal surgery patients after transfer from an ICU/high dependency unit (HDU). NEWS values were collected throughout the ward admission. Clinical deterioration was defined by ICU readmission or death. The ability of NEWS to predict clinical deterioration was determined using a linear mixed effect model. Results: We included 124 patients, age 65.9±14.5, 60% males with an ICU Simplified Acute Physiology Score II 33.8±12.7. No patients died unexpectedly at the ward and 20 were readmitted to an ICU/HDU. The NEWS values increased by a mean of 0.15 points per hour (intercept 3.7, P<0.001) before ICU/HDU readmission according to the linear mixed effect model. NEWS at transfer from ICU was the only factor that predicted readmission (OR 1.32; 95% CI 1.01–1.72; P=0.04) at the time of admission to the ward. Conclusion: Clinical deterioration of surgical patients was preceded by an increase in NEWS. Keywords: early warning score, post ICU patients, clinical deterioration, surgical